2021
DOI: 10.3390/medicina57101056
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Navigation under Local Anesthesia for Computed Tomography-Guided Microwave Ablation of Malignant Liver Lesions Located in the Hepatic Dome

Abstract: Background and Objectives: The aim of the present study was to report the safety and efficacy of percutaneous navigation under local anesthesia for computed tomography-guided microwave ablation of malignant liver lesions located in the hepatic dome. Patients with primary and secondary malignant liver lesions located in the hepatic dome who underwent percutaneous computed tomography-guided microwave ablation using a computer-assisted navigation system under local anesthesia were prospectively evaluated. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…MWA can be also combined with other locoregional therapies such as trans-arterial conventional chemoembolization, as was shown in a retrospective study which reported survival at 6, 12 and 24 months of 88.5%, 69.2% and 61.5%, respectively [48]. Furthermore, stereotactic navigation systems contribute to shortening the duration of ablation sessions by increasing the accuracy of access, even in challenging anatomic locations of the liver or for tumors located in proximity to important vasculature as well as for tumors invisible on ultrasound and CT [74,75]. Thermal ablative therapies (RFA and MWA) display promising potential as treatment modalities for iCCA with satisfactory outcome and good safety profile as was shown in published meta-analyses and systematic reviews [35,66,73] showing pooled technical efficacy of 91.9%, major complications incidence of 5.7% and pooled OS at 1, 3 and 5 years of 82.4%, 42.1% and 28.5%, respectively, with primary tumors showing higher 3-year OS rates than recurrent ones [66].…”
Section: Microwave Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…MWA can be also combined with other locoregional therapies such as trans-arterial conventional chemoembolization, as was shown in a retrospective study which reported survival at 6, 12 and 24 months of 88.5%, 69.2% and 61.5%, respectively [48]. Furthermore, stereotactic navigation systems contribute to shortening the duration of ablation sessions by increasing the accuracy of access, even in challenging anatomic locations of the liver or for tumors located in proximity to important vasculature as well as for tumors invisible on ultrasound and CT [74,75]. Thermal ablative therapies (RFA and MWA) display promising potential as treatment modalities for iCCA with satisfactory outcome and good safety profile as was shown in published meta-analyses and systematic reviews [35,66,73] showing pooled technical efficacy of 91.9%, major complications incidence of 5.7% and pooled OS at 1, 3 and 5 years of 82.4%, 42.1% and 28.5%, respectively, with primary tumors showing higher 3-year OS rates than recurrent ones [66].…”
Section: Microwave Ablationmentioning
confidence: 99%
“…MWA can be also combined with other locoregional therapies such as trans-arterial conventional chemoembolization, as was shown in a retrospective study which reported survival at 6, 12 and 24 months of 88.5%, 69.2% and 61.5%, respectively [ 48 ]. Furthermore, stereotactic navigation systems contribute to shortening the duration of ablation sessions by increasing the accuracy of access, even in challenging anatomic locations of the liver or for tumors located in proximity to important vasculature as well as for tumors invisible on ultrasound and CT [ 74 , 75 ].…”
Section: Interventional Ablative Treatment For Iccamentioning
confidence: 99%
“…Navigation systems also confirm their reliability when approaching ‘unablatable’ lesions, that are tumours situated in challenging locations (such as near large blood vessels, bile ducts, sub‐diaphragmatic or sub‐capsular regions or next proximity to nearby organs). Filippiadis et al 40 . reported a primary technical efficacy of 93.75% in ablating 16 lesions located at the hepatic dome by using a patient‐mounted device for navigation under local anaesthesia combined with intravenous analgesia.…”
Section: Imaging Guidance and Margin Assessmentmentioning
confidence: 99%
“…For robotic systems that do not insert automatically (and only guide), the actual insertion of the instruments is performed by the physician, which preserves the haptic experience, allowing for the early detection of incorrect needle positioning. Therefore, utilization of navigation and robotic systems constitutes an attractive option in the management of challenging liver tumors, such as lesions hidden in US or to non-contrast-enhanced CT, large-sized tumors, or tumors located in technically difficult locations, such as in proximity to hepatic venous confluence, diaphragm, hepatic capsule, and heart, among others [ 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Clinical Applications and The Literature Evidencementioning
confidence: 99%